ANALISIS PERAN FACEBOOK @FORUM KOMUNIKASI WARGA KROBOKAN DALAM MENINGKATKAN PELAYANAN PUBLIK DI KELURAHAN KROBOKAN JAWA TENGAH - Bayu Aji Pamungkas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes the role of Facebook as a digital communication medium in improving public services in Krobokan Village, CentralJava.The background of the study shows that the Krobokan Village government formed a Facebook group called “Krobokan Residents Communication Forum” in 2016 to overcome geographical constraints and accelerate the dissemination of information to the community. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. The research informants consisted of the Head of Services, the Head of the Hamlet,community members, and academics.The analysis was conducted using two main theoretical frameworks the, dimensions of social media, which include content, accuracy, format, ease of use, and timeliness, and the dimensions of public service, which include tangibility, reliability, responsiveness, assurance, and empathy. The results of the study show that Facebook has succeeded in increasing information transparency and accelerating access to public services by providing relevant content (agriculture, trade, entertainment, and social activities) in a language that is easily understood by all groups.However, the study also identified several significant obstacles, namely, limited internet access, inconsistency in the delivery of information on village development, and the digital divide that prevents all residents from enjoying the benefits of digital services. The recommended solutions include three main pillars, namely professionalization, integration of digital-physical services (integrated complaint system and collaboration with WiFi providers for affordable internet access), and improvement of communication quality (quality content, responsiveness, and transparency).This study concludes that although Facebook has made a positive contribution to improving public services in Krobokan Village, optimizing its use still requires improvements in responsiveness, consistency of information, and inclusiveness so that all levels of society can enjoy the same benefits.